1995
DOI: 10.1161/01.res.77.6.1192
|View full text |Cite
|
Sign up to set email alerts
|

pH i Regulation in Myocardium of the Spontaneously Hypertensive Rat

Abstract: To elucidate the mechanisms controlling pHi in myocardium of the spontaneously hypertensive rat (SHR), experiments were performed in papillary muscles (isometrically contracting at 0.2 Hz) from SHR and age-matched normotensive Wistar-Kyoto (WKY) rats loaded with the pH-sensitive fluorescent probe BCECF-AM. An enhanced activity of the Na(+)-H+ exchanger was detected in the hypertrophic myocardium of SHR. This conclusion was based on the following: (1) The myocardial pHi was more alkaline in SHR (7.23 +/- 0.03) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
1
8

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 102 publications
(57 citation statements)
references
References 47 publications
1
47
1
8
Order By: Relevance
“…In this regard, Iso-induced CH seems to differ from other models of CH in which enhanced NHE-1 activity 17,18 is not correlated with an increase in expression of the antiporter, 17,19 suggesting a role for posttranslational mechanisms. Iso-induced effects are attenuated by chronic inhibition of the exchanger.…”
Section: Discussionmentioning
confidence: 67%
“…In this regard, Iso-induced CH seems to differ from other models of CH in which enhanced NHE-1 activity 17,18 is not correlated with an increase in expression of the antiporter, 17,19 suggesting a role for posttranslational mechanisms. Iso-induced effects are attenuated by chronic inhibition of the exchanger.…”
Section: Discussionmentioning
confidence: 67%
“…Interestingly, we have found alterations in intracellular calcium handling in ␤ 1 -adrenergic receptor transgenic mice that are similar to human heart failure and include markedly prolonged calcium transients. 15 Furthermore, increased NHE1 activity has been demonstrated in the myocardium of spontaneously hypertensive rats 21,22 and after treatment of cardiac myocytes with hypertrophic agonists of Gq-coupled pathways such as endothelin, 23 angiotensin, 24 and thrombin. 25 Takewaki et al 26 showed in cultured myocytes that NHE inhibition partially inhibited stretch-induced activation of MAP-kinases and activation of MAP-kinases was linked to hypertrophic signaling of adrenergic receptors.…”
Section: Engelhardt Et Al Nhe Inhibition In ␤ 1 -Receptor Transgenic mentioning
confidence: 99%
“…Enhanced activity of the NHE1 was first reported in the hypertrophic myocardium of spontaneously hypertensive rats by Perez et al (47). Thereafter, NHE1 protein expression and activity have been demonstrated to be elevated in a variety of cardiovascular diseases, including in hypertensive, hypertrophied, and diabetic myocardium (7,18,30,32), in hearts subjected to ischemia (24), in isolated cardiomyocytes subjected to chronic acidosis (16), and in patients with end-stage heart failure (55).…”
mentioning
confidence: 99%